Iron/copper metabolism in Alzheimer’s disease: genetics and biomarkers in a Portuguese population - C. Crespo, Ângela (2013)
This work was supported by Fundação Astrazeneca through the “Programa de Apoio à Investigação” . Presented at the “International Conference in Alzheimer’s Disease 2009